Development of Maritime Professionals in Bangladesh: A Literature Review - Hossain, Mohammad Morad; Islam, Prof. Dr. Md. Nazrul (International Journal of Scientific Research and Management (IJSRM), 2021)
Bangladesh has a rich shipping history. The country is dependent economically as well as socially and politically on the industry. While, the country is slowly regaining global recognition, the industry is no less on challenges. The seafarers face major issues due to the factors such as conditions of the maritime education and training institutes, forged documentation, negative reputation of the country, etc. Further, the seafarers of Bangladesh also lack skills and training when compared to the seafarers of the other developed countries. Moreover, the country lacks technological resources too, which makes it even more difficult for the seafarers to grow in the industry. The article looked at the different sets of improvements that can be made to the shipping industry and make it easy for the seafarers to get proper jobs in the industry. This study explored the challenges and opportunities for the seafarers and the industry though a review of literature.